Orchid diversity at a residual plateu on Caroebe, Roraima - Francisco Joaci de Freitas Luz; Jane Maria Franco de Oliveira; Gladis de Fátima Nunes da Silva (Ornamental Horticulture, 2016)
Orchids were observed in a granitic mountain hill at the, Caroebe road 35, Roraima, at February and June of 2016. It was observed the occurrence of orchids in three different points: the base of the mountain, with typical humid tropical dry land forest; the forest around the rocky top of the mountain, with the presence of thin trees about 15 meters high, medium light entrance below the vegetation; and the granitic plateau, more sun incidence and surrounded by small shrubs. The total area surveyed was of 5 hectares. The orchids encountered in the whole trail were prior identified locally, just as their localization by GPS and according to their growth habit (epiphytic, terrestrial or rupicolous). It was found 28 species. The majority of the indivíduals identified in this survey were found on organic layers accumulated over the granitic rock, as follow: Catasetum planiceps, Catasetum discolor, Cyrtopodium andersonii, Encyclia granitica, Epidendrum ibaguense, Epidendrum viviparum, Cleistes rosea e Nohawilliamsia pirarensis. At the forest that surrounds the rocky hill it was observed, associated to small trees, the following epiphyte orchids: Dimerandra emarginata, Octomeria sp., Scaphyglottis sickii, Trigonidium acuminatum and Cattleya violacea. At the forest covering the base of the mountain it was found the larger number of species (13), with predominance of epiphytes. Besides the larger number found, the frequency of these species was very low, except for Camaridium ochroleucum and Heterotaxis superflua that were found in larger quantity associated to some sort of trees. The specie Liparis nervosa was found only associated to the base of a unique tree, over the organic matter accumulated locally. The large number of orchids found in the study area indicates its importance for more comprehensive studies and stresses the importance for conservation.